Malpractice in the public sector and its impact on labor outsourcing: a critical analysis for innovation in public management - de Araujo, Edna Torres (Eximia, 2024)
This study investigates dishonesty in the public sector and the outsourcing of labor as a management solution, seeking to understand its impact on the efficiency and motivation of civil servants. Using an exploratory qualitative approach, semi-structured interviews were conducted with civil servants from five public organizations in northern Brazil. The results indicate that slacking off results from a disconnection between organizational objectives and the expectations of civil servants, a lack of recognition and limitations in the development of competencies. Although outsourcing is adopted as an immediate response to a lack of motivation, the study reveals that it has long-term negative consequences, including the loss of intellectual capital and the weakening of organizational culture. The article proposes an intervention framework based on appreciation, human development, encouraging autonomy and clear communication. This framework aims to promote management practices that reduce absenteeism and improve employee engagement. The relevance of this study lies in expanding the understanding of the relationship between organizational culture and motivation in the public sector, highlighting the impact of outsourcing on internal cohesion and proposing a more sustainable management model. Recommendations include training managers, implementing continuous recognition practices and promoting autonomy. Limitations of the study involve the sample being restricted to a specific region and the absence of quantitative data. Future research could expand these findings to other contexts and evaluate the effectiveness of the proposed framework, with a view to improving public management and the quality of the services provided.